STRUCTURAL AND CHEMICAL HETEROGENEITY OF LAYER SILICATES AND CLAY MINERALS - Drits V.A. (My University, 2003)
Different forms of structural and chemical heterogeneity are considered including mixed-layer minerals, disordered layer structures containing rotational and translational stacking faults, interstratification of trans-vacant(tv)and cis-vacant(cv) layers in true micas, illites and illite-smectite (I-S), short-range order in isomorphous cation distribution etc. Because determination of various structural and chemical imperfections requires elaboration of new diffraction and spectroscopic methodologies, special attention is paid to recent achievements in the development of new methodological approaches such as a multispecimen simulation of experimental X-ray diffraction (XRD) patterns from mixed-layer minerals, with account taken of layer-thickness fluctuations of the second type and possible difference between structures of outer and core-layers; experimental determination of thickness distribution of illite crystals by HRTEM and the modified Bertaut-Warren-Averbach technique; XRD and thermal methods for determination of cv and tv layers in true micas, illites and I-S; generalization of Méring's rules to account for the behaviour of non-basal reflections for any defective structure in which two translations are irregularly interstratified; various ab initio calculations devoted to modelling infrared OH vibrations, octahedral cation distribution in dioctahedral 2:1 layer silicates, etc.It is shown that these recently-developed methodologies have revealed new diversity in the structural and chemical heterogeneity of phyllosilicates and clay minerals, provided new insight into the structural mechanisms of their transformation in different geological environments, and discovered new natural processes.
Keywords: heterogeneity; layer silicates; clay minerals; mixed layers; illite; illite-smectite; mica